Applied mineralogy applications in industry and environment - Mukherjee, Swapna; SpringerLink (Online service). (Dordrecht New York New Delhi, India Springer Capital Publishing Co., 2011)
This book covers the entire spectrum of mineralogy and consolidates its applications in different fields. Part I starts with the very basic concept of mineralogy describing in detail the implications of the various aspects of mineral chemistry, crystallographic structures and their effects producing different mineral properties. Part II of the book describes different aspects of mineralogy like geothermobarometry, mineral thermodynamics and phase diagrams, mineral exploration and analysis, and marine minerals. Finally Part III handles the applications in industrial, medicinal and environmental mineralogy along with precious and semiprecious stone studies. The various analytical techniques and their significance in handling specific types of mineralogical problems are also co
Introduction -- Part-I: Essentials of Mineralogy -- Minerals and Their Chemical Classification -- Mineral Crystals and Structural Classification -- Mineral Chemistry -- Physical Properties -- Optical Mineralogy and Its Uses -- Special Mineral Properties and Related Structures -- Descriptive Mineralogy -- Part ? II: Mineral Transformations and Their Effects -- Energetics, Thermodynamics and Stability of Minerals -- Origin of Minerals and Their Transformations in Nature under various Environmental Conditions -- Mineral Deposits and Their Characteristics -- Marine Minerals in Different Environments -- Minerals and Mineral Associations as Geothermometers and Geobarometers -- Part-III: Mineral Analysis, Industry and Environment -- Common Analytical Techniques in Mineralogical Studies -- Precious and Semiprecious Stones -- Mineralogy in Exploration of Mineral Deposits using Magnetic, Electrical and Gravitational Properties -- Synthesis of Selected Minerals (Crystals) in Laboratory and Industry -- Industrial Mineralogy: Mineral Processing, Beneficiations and Other Related Mineral Usage -- Environmental Mineralogy -- Concept of Geomedicine and Medicinal Mineralogy.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Mineralogy; Mineralogy -- Problems, exercises; Electronic books